2020
DOI: 10.3390/w12102695
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation in Phytoplankton Community Driven by Environmental Factors in the Northern East China Sea

Abstract: The East China Sea (ECS) is the largest marginal sea in the northern western Pacific Ocean. In comparison to various physical studies, little information on the seasonal patterns in community structure of phytoplankton is currently available. Based on high performance liquid chromatography (HPLC) pigment analysis, spatiotemporal variations in phytoplankton community compositions were investigated in the northern ECS. Water temperature and salinity generally decreased toward the western part of the study area b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 68 publications
4
11
0
Order By: Relevance
“…Cryptophytes contribute to total chlorophyll-a concentrations and are mainly distributed in coastal areas of the ECS (Gao and Song, 2005). However, in recent studies, cryptophytes were found in the entire ECS (Liu et al, 2016) and were confirmed as one of the main contributors in autumn and winter 2018 (Kim et al, 2020). In this study, we first observed that cryptophytes replaced diatoms in the NECS and were the dominant species in autumn and winter 2020.…”
Section: Diatoms and Cryptophytesmentioning
confidence: 51%
See 4 more Smart Citations
“…Cryptophytes contribute to total chlorophyll-a concentrations and are mainly distributed in coastal areas of the ECS (Gao and Song, 2005). However, in recent studies, cryptophytes were found in the entire ECS (Liu et al, 2016) and were confirmed as one of the main contributors in autumn and winter 2018 (Kim et al, 2020). In this study, we first observed that cryptophytes replaced diatoms in the NECS and were the dominant species in autumn and winter 2020.…”
Section: Diatoms and Cryptophytesmentioning
confidence: 51%
“…These water masses provide most of the nutrients for the growth of phytoplankton in the NECS (Furuya et al, 2003;Chen, 2009).Therefore, separate analyses after dividing water masses according to temperature and salinity, have become mainstream in previous studies in the ECS Yoon et al, 2015;Liu et al, 2018;Xu et al, 2019). This approach led to ideal results for short-term seasonal variations in phytoplankton community structure (Liu et al, 2016;Kim et al, 2020) and the long-term interannual variations in summer when the water mass was well stratified (Xu et al, 2019). However, the different water mass-based analyses were not applicable to this study because in all of the seasons, except summer, the water column was mixed during this study period from 2018 to 2020.…”
Section: Discussion Previous Studies and A New Methodsmentioning
confidence: 99%
See 3 more Smart Citations